Development Operation and Characterization of Cesium Beam Atomic Clock - Imran, M.; Ikram, M.; Islam, R. U.; Anwar, M.; Tariq, H.; Ahmad, M. (The Nucleus, 2020)
We report the development, operation and characterization procedure of the first ever Cesium Atomic Beam Clock in Pakistan. The importance of the National Time and Frequency standards is duly highlighted in the context of a developing country. The active program spans a time of about three years and the Ramsey Interferometric signals, i.e., the fundamental physical phenomenon, recorded recently depict a 25 kHz broad Rabi profile incorporating a much narrower Ramsey fringe having width of about 800 Hz only clearly demonstrate a clean, smooth, stable and accurate operation of the clock.